Concurrent validation of an active therapeutic molecule for Type II diabetes by Reverse Phase- High Performance Liquid Chromatography: A Quality Assessment Approach - G. Ramya Priy; R. B. Nalanda; H. Atchyut (The Bioscan, 2026)
Background: Canagliflozin is an important therapeutic agent used in the management of Type II diabetes mellitus. Although several analytical methods have been reported for its simultaneous estimation with other drugs, dedicated methods for its individual quantitative assessment remain limited. Objective: The present study aimed to develop and concurrently validate a robust, precise, and stability- indicating RP-HPLC method for the quantitative estimation of Canagliflozin. Methods: Chromatographic separation was performed using a C18 column (4.6 mm × 250 mm, 5 μm) with a mobile phase consisting of formic acid and acetonitrile (45:55, v/v) under isocratic conditions. The flow rate was maintained at 1.1 mL/min, and detection was carried out at 290 nm. The developed method was validated according to standard analytical parameters, including specificity, linearity, precision, accuracy, robustness, and forced degradation studies. Results: The developed method exhibited a retention time of 5.8 min and demonstrated excellent linearity over the concentration range of 1–30 μg/mL with a correlation coefficient (R²) of 0.9988. The limits of detection (LOD) and quantification (LOQ) were determined to be 0.177 μg/mL and 0.536 μg/mL, respectively. Validation results confirmed the method's specificity, precision, accuracy, robustness, and stability-indicating capability Conclusion: The validated RP-HPLC method was found to be reliable, sensitive, and suitable for routine quality control analysis of Canagliflozin. Furthermore, the method can be extended to future bioanalytical and pharmacokinetic studies involving Canagliflozin in pharmaceutical and biological matrices.